Collaborative planning via urban agriculture: The case of Tegucigalpa, Honduras. Issue 8 (14th September 2017) - Oyuela, Andrea; Van Der Valk, Arnold
ABSTRACT: The city of Tegucigalpa as it is today is a result of the rural–urban migration phenomenon triggered in the 1950s across Honduras and the accompanying blueprint models of urban development at the time. Nowadays, the city is dominated by issues such as social disparity, urban violence, and environmental degradation. We question the adequacy of Tegucigalpa's top–down planning system and explore the concept of urban agriculture (UA) as a multifaceted lever that can provide building blocks for an alternative bottom–up strategy to address the intricate web of problems the city faces. Noteworthy among our discoveries is the potential of school gardens to serve as a channel for strategically achieving community goals. UA is organized as a result of residents' need to overcome food insecurity and hardship in the city. Still, the topic of active citizenship and bottom–up development is not yet consolidated in the context of Tegucigalpa. Moreover, the city poses challenges regarding the resources needed for practicing UA and the diffusion of knowledge to the population. Nevertheless, steps must be taken toward further considering UA and its social assets that may compensate for the unfavorable access to resources in the urban area.